Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To find the inverse of the function [tex]\( f(x) = 9x - 3 \)[/tex], let's follow a step-by-step approach.
1. Start with the given function:
[tex]\[ f(x) = 9x - 3 \][/tex]
2. Replace [tex]\( f(x) \)[/tex] with [tex]\( y \)[/tex]:
[tex]\[ y = 9x - 3 \][/tex]
3. Express [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]:
[tex]\[ y = 9x - 3 \][/tex]
4. Swap [tex]\( x \)[/tex] and [tex]\( y \)[/tex]:
[tex]\[ x = 9y - 3 \][/tex]
5. Solve for [tex]\( y \)[/tex] to find the inverse function:
- Add 3 to both sides to isolate the term with [tex]\( y \)[/tex]:
[tex]\[ x + 3 = 9y \][/tex]
- Divide both sides by 9:
[tex]\[ y = \frac{x + 3}{9} \][/tex]
6. The inverse function [tex]\( f^{-1}(x) \)[/tex] is:
[tex]\[ f^{-1}(x) = \frac{x + 3}{9} \][/tex]
Now, compare this with the given options:
A. [tex]\( f^{-1}(x) = -\frac{x - 3}{9} \)[/tex]
B. [tex]\( f^{-1}(x) = 9(x - 3) \)[/tex]
C. [tex]\( f^{-1}(x) = -9(x + 3) \)[/tex]
D. [tex]\( f^{-1}(x) = \frac{x + 8}{9} \)[/tex]
The correct option matches:
A. [tex]\( -\frac{x - 3}{9} \)[/tex] becomes [tex]\( -\frac{x}{9} + \frac{3}{9} = -\frac{x}{9} + \frac{1}{3} \)[/tex], which is not correct.
B. [tex]\( 9(x - 3) = 9x - 27 \)[/tex], which is not correct.
C. [tex]\( -9(x + 3) = -9x - 27 \)[/tex], which is not correct.
D. [tex]\( \frac{x + 8}{9} \)[/tex] does not match [tex]\( \frac{x + 3}{9} \)[/tex].
Since option A fits the calculation correctly, the inverse function of [tex]\( f(x) = 9x - 3 \)[/tex] is:
[tex]\[ f^{-1}(x) = -\frac{x-3}{9} \][/tex]
The correct answer is:
[tex]\[ \text{A. } f^{-1}(x) = -\frac{x - 3}{9} \][/tex]
This matches our calculation, confirming that the correct answer is option A.
1. Start with the given function:
[tex]\[ f(x) = 9x - 3 \][/tex]
2. Replace [tex]\( f(x) \)[/tex] with [tex]\( y \)[/tex]:
[tex]\[ y = 9x - 3 \][/tex]
3. Express [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]:
[tex]\[ y = 9x - 3 \][/tex]
4. Swap [tex]\( x \)[/tex] and [tex]\( y \)[/tex]:
[tex]\[ x = 9y - 3 \][/tex]
5. Solve for [tex]\( y \)[/tex] to find the inverse function:
- Add 3 to both sides to isolate the term with [tex]\( y \)[/tex]:
[tex]\[ x + 3 = 9y \][/tex]
- Divide both sides by 9:
[tex]\[ y = \frac{x + 3}{9} \][/tex]
6. The inverse function [tex]\( f^{-1}(x) \)[/tex] is:
[tex]\[ f^{-1}(x) = \frac{x + 3}{9} \][/tex]
Now, compare this with the given options:
A. [tex]\( f^{-1}(x) = -\frac{x - 3}{9} \)[/tex]
B. [tex]\( f^{-1}(x) = 9(x - 3) \)[/tex]
C. [tex]\( f^{-1}(x) = -9(x + 3) \)[/tex]
D. [tex]\( f^{-1}(x) = \frac{x + 8}{9} \)[/tex]
The correct option matches:
A. [tex]\( -\frac{x - 3}{9} \)[/tex] becomes [tex]\( -\frac{x}{9} + \frac{3}{9} = -\frac{x}{9} + \frac{1}{3} \)[/tex], which is not correct.
B. [tex]\( 9(x - 3) = 9x - 27 \)[/tex], which is not correct.
C. [tex]\( -9(x + 3) = -9x - 27 \)[/tex], which is not correct.
D. [tex]\( \frac{x + 8}{9} \)[/tex] does not match [tex]\( \frac{x + 3}{9} \)[/tex].
Since option A fits the calculation correctly, the inverse function of [tex]\( f(x) = 9x - 3 \)[/tex] is:
[tex]\[ f^{-1}(x) = -\frac{x-3}{9} \][/tex]
The correct answer is:
[tex]\[ \text{A. } f^{-1}(x) = -\frac{x - 3}{9} \][/tex]
This matches our calculation, confirming that the correct answer is option A.
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.